Development of framework to increase flexibility in shop floor and maximize production rate using substitute machine - Kumar, Pagare Ajay; Neeraj, Kumar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The research attempt to increase flexibility in shop floor and improve rate of production through maintenance engineering policies. The research is grounded on analysis of data collected from manufacturing based MSMEs and review of literature and data of spare parts published in referred journals. The study derives a further framework model comprising three strategies (Supply chain management, inventory management, and maintenance engineering) to improve rate of production. The aforesaid process is used to identify problems that occur during machine breakdown. The paper provides a research substitute machine to manage problems during breakdown of machines so that production is not hindered.